2009
DOI: 10.1111/j.1365-3156.2009.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Judging respiratory specimen acceptability for AFB microscopy: visual vs. microscopic screening

Abstract: Summaryobjectives To investigate whether visual assessment or microscopic grading of the cellular composition of specimens is a better strategy to screen specimen quality for tuberculosis (TB) diagnosis.methods About 2643 specimens were collected from TB suspects at the Federal TB centre in Pakistan. Specimens were classified as sputum or saliva visually and microscopically using the criteria proposed by McCarter and Robinson, Van Scoy, Geckler et al., Murray and Washington and Bartlett. The acid-fast bacilli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
7
1
1
Order By: Relevance
“…The poor performance of macroscopic assessment found in our study differs from the observation by Kahn et al, who stated that macroscopic assessment was a valid approach for identification of smear-positive respiratory specimens [9]. This conclusion was based on the fact that macroscopic assessment rejected the least number of specimens in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The poor performance of macroscopic assessment found in our study differs from the observation by Kahn et al, who stated that macroscopic assessment was a valid approach for identification of smear-positive respiratory specimens [9]. This conclusion was based on the fact that macroscopic assessment rejected the least number of specimens in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Using these algorithms for assessing the possibility for adequate AFB microscopy has been much less examined. A previous study on the usefulness of macroscopic assessment of respiratory specimens for AFB diagnosis was carried out in a routine TB diagnostic setting [9]. This implies a passive case finding strategy in which individuals report themselves to a health facility because of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al (128) found that, despite being the least technical and time-consuming method, visual assessment to determine whether the specimen is sputum or saliva rejected the lowest proportion of AFB-positive specimens (0.3%). Most microscopic grading criteria, particularly those that considered the squamous epithelial cell count, rejected a large proportion of specimens (30 to 66%), a sizeable fraction of which contained AFB (6 to 12%).…”
Section: Acceptable Specimens and Rejection Criteriamentioning
confidence: 99%
“…Considering that WHO plans to change the current “spot-morning” sputum submission to “spot-spot” sputum submission for smear microscopy [9,10] and that the smear positivity yield of spot sputum is lower than that of morning sputum [11], development of quality criteria that could guarantee sputum specimens of adequate quality is crucial. Although various kinds of quality criteria regarding specimen gross appearance and volume [3-6,8,12-14] are recommended to be checked upon collection, these criterias are based not on a well-designed study, but on expert opinion [15]. The purpose of this study was to elucidate the impact of sputum specimen gross appearance and volume on smear positivity in patients suspected to have pulmonary TB, according to sex.…”
Section: Introductionmentioning
confidence: 99%